2017
DOI: 10.18632/oncotarget.20689
|View full text |Cite
|
Sign up to set email alerts
|

Extracts fromHericium erinaceusrelieve inflammatory bowel disease by regulating immunity and gut microbiota

Abstract: Hericium erinaceus (HE), a traditional edible mushroom, is known as a medicine food homology to ameliorate gastrointestinal diseases. To investigate whether HE is clinically effective in alleviating inflammatory bowel disease (IBD), HE extracts (polysaccharide, alcoholic extracts and whole extracts were prepared using solvent extraction methods) were administrated for 2 weeks in rats with IBD induced by trinitro-benzene-sulfonic acid (TNBS) enema (150 mg/kg). Significant clinical and histological changes in IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 64 publications
5
41
0
Order By: Relevance
“…We observed distinct microbial communities within the different groups. Dorea is a potentially pro-inflammatory taxa ( Diling et al, 2017 ), and was significantly increased in C. sinensis infected subjects. This increase was also observed in other helminth infected individuals ( Duarte et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed distinct microbial communities within the different groups. Dorea is a potentially pro-inflammatory taxa ( Diling et al, 2017 ), and was significantly increased in C. sinensis infected subjects. This increase was also observed in other helminth infected individuals ( Duarte et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 Further studies assessed the efficacy of H. Erinaceous extract in Helicobacter pylori activity, 32 chronic gastritis, 33 IBD. 34 Our study showed good outcomes after intake of H.Erinaceous supplements in patients with different gastrointestinal diseases, and the satisfaction of participants was 6 from 10 (18.8%).…”
Section: The Role Of Lion's Mane Mushroom Mane In Cancermentioning
confidence: 56%
“…A single protein, called HEP3, isolated from H. erinaceus and administered to rats treated with trinitrobenzenesulfonic acid (TNBS) to induce experimental colitis similar to IBD, was capable of restoring the microbiota diversity in treated rats. In particular, treatment with H. erinaceus single protein increased the amounts of Actinobacteria and Tenericutes, reduced those of Bacteroidetes and Firmicutes, and was able to restore a healthy-like ecological structure [128,129]. The effectiveness of HEP3 was also confirmed in other animal models of colitis [130].…”
Section: Microbiota-modulating Fungimentioning
confidence: 92%
“…Also, raw extracts of H. erinaceus were tested in an IBD animal model as whole polysaccharide, alcoholic extract or whole extract. Results indicate that all these formulations were capable of positively modulating the microbiota, but while the polysaccharide extract seems to play a major prebiotic role, the alcoholic extract and whole extract showed major bactericidin-like effects [128,129].…”
Section: Microbiota-modulating Fungimentioning
confidence: 99%